An analysis of patterns of distribution of buprenorphine in the United States using ARCOS, Medicaid, and Medicare databases - Zhi‐Shan Hsu; Justina A. Warnick; Tice R. Harkins; Briana E. Sylvester; Neal K. Bharati; leTausjua B. Eley; Stephanie D. Nichols; Kenneth McCall; Brian J. Piper (Wiley, 2023)
Abstract Opioid overdose remains a problem in the United States despite pharmacotherapies, such as buprenorphine, in the treatment of opioid use disorder. This study characterized changes in buprenorphine use. Using the Drug Enforcement Administration's ARCOS, Medicaid, and Medicare claims databases, patterns in buprenorphine usage in the United States from 2018 to 2020 were analyzed by examining percentage changes in total grams distributed and changes in grams per 100 K people in year‐to‐year usage based on ZIP code and state levels. For ARCOS from 2018 to 2019 and 2019 to 2020, total buprenorphine distribution in grams increased by 16.2% and 12.6%, respectively. South Dakota showed the largest statewide percentage increase in both 2018-2019 (66.1%) and 2019-2020 (36.7%). From 2018 to 2019, the ZIP codes ND‐577 (156.4%) and VA‐222 (−82.1%) had the largest and smallest percentage changes, respectively. From 2019 to 2020, CA‐932 (250.2%) and IL‐603 (−36.8%) were the largest and smallest, respectively. In both 2018-2019 and 2019-2020, PA‐191 had the second highest increase in grams per 100K while OH‐452 was the only ZIP code to remain in the top three largest decreases in grams per 100K in both periods. Among Medicaid patients in 2018, there was a nearly 2000‐fold difference in prescriptions per 100k Medicaid enrollees between Kentucky (12 075) and Nebraska (6). Among Medicare enrollees in 2018, family medicine physicians and other primary care providers were the top buprenorphine prescribers. This study not only identified overall increases in buprenorphine availability but also pronounced state‐level differences. Such geographic analysis can be used to discern which public policies and regional factors impact buprenorphine access.